Seismic performance investigation of an innovative steel shear wall with semi-rigid beam-to-column connections - Abdul Ghafar, Wahab; Zhong, Tao; Abid, Muhammad; Faizan, Enamullah; Mohamed, Abdullah; Yosri, Ahmed M. (Frontiers in Materials, 2022)
Steel plate shear walls (SPSWs) are a robust lateral load resistance structure because of their high ductility and efficient energy dissipation when subjected to seismic loads. This research investigates the seismic performance of an innovative infill web strip (IWS-SPSW) and a typical unstiffened steel plate shear wall (USPSW). As a result, two 1:3 scale specimens of an IWS-SPSW and USPSW with a single story and a single bay were built and subjected to a cyclic lateral loading methodology. In the prototype, semi-rigid end-plate connectors for the beam-to-column connections were utilized. The test result of IWS-SPSW showed outstanding ductility and shear load-bearing capacity without cracks or damage. Additionally, the IWS-SPSW exhibited strong energy dissipation without substantial beam-column connection distortion. USPSW showed excellent shear load-bearing capacity, low ductility, extensive infill plate corner tearing, and large infill web plate cracks. The FE models were verified against experimental data after development. It has been shown that the infill web strips can affect the high performance and overall energy dissipation of an SPSW system. In addition, a parametric study was conducted to investigate the “infill web strip material properties,” such as steel strength and thickness, that can significantly enhance the system's seismic performance.